2021
DOI: 10.7759/cureus.16139
|View full text |Cite
|
Sign up to set email alerts
|

Twinning: Coronary Artery Disease in Monozygotic Twins

Abstract: We present the case of a patient whose monozygotic twin brother suffered a fatal myocardial infarction at the age of 40. The patient presented with similar symptoms as his brother. Given the family history, ischemic evaluation was undertaken and revealed similar coronary anatomy and severe coronary artery disease (CAD). We review the current literature regarding genetic and environmental factors regarding coronary anatomy, locations of atherosclerotic lesions, and screening in twins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…On the other hand, genetic predisposition can be modified by different factors such as physical activity (34). Various studies have shown the importance of genetic predisposition in developing CDs by carrying out comparative studies between monozygotic or dizygotic twins against unrelated individuals, showing a higher prevalence of type 2 diabetes (35) and CVDs between twins (36,37).…”
Section: Genetic Factorsmentioning
confidence: 99%

Chronic diseases: Origin and cell mechanisms involved

David Hernán Martínez-Puente,
Carlos Saúl Rodríguez-Roque,
Laura Mireya Flores-Zavala
et al. 2023
Cell Mol Biol (Noisy-le-grand)
“…On the other hand, genetic predisposition can be modified by different factors such as physical activity (34). Various studies have shown the importance of genetic predisposition in developing CDs by carrying out comparative studies between monozygotic or dizygotic twins against unrelated individuals, showing a higher prevalence of type 2 diabetes (35) and CVDs between twins (36,37).…”
Section: Genetic Factorsmentioning
confidence: 99%

Chronic diseases: Origin and cell mechanisms involved

David Hernán Martínez-Puente,
Carlos Saúl Rodríguez-Roque,
Laura Mireya Flores-Zavala
et al. 2023
Cell Mol Biol (Noisy-le-grand)
“…This is supported by various evidence from twin studies. [7][8][9][10][11] The complex genetic inheritance of AMI can be explained by one of the major twin studies in Sweden involving 2,341 first-episode cases of AMI which concluded the contribution of genetic variants to the disease, while additional genetic factors contribute to the disease phenotypes. 12 An underlying genetic predisposition is much more relevant to those who develop AMI at a young age.…”
Section: Introductionmentioning
confidence: 99%